Factors Associated with Stunting among Children Under Five: a Cross-Sectional Study in Southwest Papua, Indonesia - Maria Loihala; Wa Ode Likewati (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: one of the most worrying long term impacts of child marriage is the high rate of stunting among under-fives which is still prevalent in many areas, including in Southwest Papua. This study aims to analyze the associative relationship between stunting and child marriage in Klalin District, Sorong Regency, Southwest Papua. Methods: a cross-sectional approach was adopted for this research, and the research was performed from June to September 2025. The research involved 113 families selected with cluster sampling techniques at 4 areas in Klalin District using the Lameshow formula. Chi-square and multiple binary regression analyses were applied in this study. Results: most mothers who married under 18 years old had a junior high school education (41.6%) and were not employed (52.2%). In multivariate analysis, maternal age under 18 years was significantly associated with stunting (AOR = 2.72; 95% CI: 1.17–6.32; p = 0.020). Low maternal education was also significantly associated with stunting (AOR = 1.69; 95% CI: 1.16–2.47; p = 0.007), while maternal occupation was not significantly associated with stunting (AOR = 1.15; 95% CI: 0.93–1.41; p = 0.198). Conclusion: child marriage among girls under 18 is prevalent in Southwest Papua and is significantly associated with low maternal education, which is also associated with an increased risk of stunting in children. These findings suggest that stunting prevention strategies should prioritize efforts to delay the age of marriage and improve women’s educational attainment, alongside initiatives to enhance women’s economic opportunities.